2020
DOI: 10.1080/15257770.2020.1826516
|View full text |Cite
|
Sign up to set email alerts
|

Efficient one-pot, three-component procedure to prepare new α-aminophosphonate and phosphonic acid acyclic nucleosides

Abstract: Efficient one-pot, three components procedure to prepare new αamino phosphonate and phosphonic acid acyclic nucleosides An efficient one-pot three-component Kabachnick-Fields reaction of aldehydes (acyclic nucleosides), amines (or amino acid), and triethylphosphite proceeded for the synthesis of amino phosphonates using natural phosphate coated with iodine (I 2 @NP) as a catalyst. The novel α-aminophosphonate and phosphonic acid acyclic nucleosides were tested for their anti-HCV and anti-HIV activities.The mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Moreover, alongside the after-mentioned interactions for ligand 7 b, the introduction of thiazole in compound 7 b showed two additional Pi-sulfur and PiÀ Pi T-shaped into reactions with Cys163 and His121, which are among the key amino acids responsible for the caspase-3 activation. [50][51][52][53][54][55] Overall, molecular docking suggested that the anticancer activities of products 2 b and 7 b could be at least mediated by activating caspase-3 protein after binding to its active site.…”
Section: Molecular Docking Studymentioning
confidence: 99%
“…Moreover, alongside the after-mentioned interactions for ligand 7 b, the introduction of thiazole in compound 7 b showed two additional Pi-sulfur and PiÀ Pi T-shaped into reactions with Cys163 and His121, which are among the key amino acids responsible for the caspase-3 activation. [50][51][52][53][54][55] Overall, molecular docking suggested that the anticancer activities of products 2 b and 7 b could be at least mediated by activating caspase-3 protein after binding to its active site.…”
Section: Molecular Docking Studymentioning
confidence: 99%
“…The ligand structure was created separately using ChemDraw Ultra 12.0, energy was minimized in Chem3D, and torsional bonds of the ligand were set to be flexible and saved in PDBQT format. [ 60 ] Next, the receptor was kept rigid and a grid covering all the amino acid residues present inside the active site of proteins was built (grid box size of 50 × 50 × 50 Å with a spacing of 0.375 Å between the grid points and centered at 35.58 [ x ], 94.397 [ y ], and 17.54 [ z ]). The best conformers were searched using the Lamarckian genetic algorithm, the population size was set to 150, and the maximum number of energy evaluations was set to 25,000,000.…”
Section: Methodsmentioning
confidence: 99%
“…Amines have also been employed for the synthesis of various α-amino phosphonates 126 via iodine catalyzed MCRs. A Kabachnik-Field reaction of amines, acyclic nucleosides and triethyl phosphate was reported by Baddi et al [124] in one-pot manner using natural phosphate coated with iodine (I 2 @NP) as catalyst (Scheme 63). Aromatic as well as aliphatic amines reacted smoothly to furnish the corresponding α-amino phosphonates 126 in good yield.…”
Section: Synthesis Of Isoquinolonic Acids Phosphonic Acid Acyclic Nuc...mentioning
confidence: 99%